Post-activation performance enhancement in resisted sprinting: effects of different loads and rest intervals on 100-m sprint segments - Chen, Weixiong; Qian, Dexing; Zhang, Huaichuan; Shen, Yanfei (Frontiers in Physiology, 2025)
This study aimed to investigate the acute effects of resisted sprint-induced post-activation potentiation enhancement (PAPE) on 100-m sprint performance under three loading conditions (5%, 10%, and 15% body weight) and three rest intervals (4, 8, and 12 min), with a focus on segmental performance (0–30 m, 30–60 m, and 60–100 m). In a randomized crossover design, ten male college sprinters (age: 19.2 ± 1.5 years; 100-m personal best: 11.31 ± 0.30 s) performed nine experimental tests over 19 days. Each trial included a 40-m resisted sprint using the motorized Jueying™ system (Beijing Sport University) followed by a 100-m sprint under one of the nine load-rest combinations. Sprint times were measured via SmartSpeed™ timing gates. The 10% BW load with an 8-min rest interval elicited the greatest PAPE effect, significantly improving performance in the 0–30 m (Δ = 0.192 s, p < 0.01; Cohen’s d = 1.66) and 30–60 m (Δ = 0.154 s, p < 0.05; d = 1.29) segments. However, no significant improvements were observed in the 60–100 m segment. The loads of 5% and 15% BW showed smaller or inconsistent effects in the rest intervals.